Systematic review of monotherapy with biologicals for children and adults with IgE‐mediated food allergy - Debra de Silva; Chris Singh; Stefania Arasi; Antonella Muraro; Torsten Zuberbier; Motohiro Ebisawa; Montserrat Alvaro Lozano; Graham Roberts (Clinical and Translational Allergy, 2022)
Abstract Background Biological therapies relieve symptoms in allergic inflammatory diseases so we systematically reviewed the evidence about whether biological monotherapy could benefit people with IgE‐mediated food allergy. Methods We searched six bibliographic databases from 1946 to 30 September 2021 for randomised and non‐randomised controlled trials about biological monotherapy in people with IgE‐mediated food allergy confirmed by oral food challenge. We used the Grading of Recommendations, Assessment, Development and Evaluation approach to narratively summarise findings from three trials with 118 participants. The studies were too heterogeneous and sparse to conduct meta‐analysis. Results We included one randomised trial about etokimab, one about omalizumab and one about the discontinued TNX‐901. All were in people with peanut allergy in the USA, mostly aged 13+ years. There was a trend towards improved tolerance of peanut during treatment, with few side effects. However, we have very low certainty about the evidence due to the small number of trials and participants. No included trial reported on quality of life or cost‐effectiveness. Conclusions There is not yet enough certainty to support offering etokimab or omalizumab widely for food allergy. Clinicians may consider the merits for individuals, but large randomised trials with standardised measures are needed to confirm the safety, efficacy and most suitable candidates, doses and durations of treatment before more universal use.